Graphic User Interface (GUI) untuk materi dinamika gerak sistem katrol berbasis matlab - Alpi Mahisha Nugraha (Navigation Physics : Journal of Physics Education, 2019)
Learning physics will be less optimal if the teacher teaches based on the textbook. Other alternative media are needed to increase the student interesting in learning and make the student can studies easier. Especially fundamental chapters such as the dynamics of motion, like pulley systems. Because in those problems, it involves both of the dynamics in translation and rotational motion. Using Matlab-based on Graphic User Interface (GUI) is expected to increase student’s interesting and understanding of the problems in the pulley system. Because students just only enter the required input data and adjust the desired system conditions to calculate the quantities asked for that problem. Furthermore, the designed GUI can present a brief and concise explanation with easy language to understand by students about the phenomenon and students can also see the formula used in the pulley system problem.